Breathable Artificial Interphase for Dendrite‐Free and Chemo‐Resistive Lithium Metal Anode. Issue 8 (9th December 2021) - Song, Gyujin; Hwang, Chihyun; Song, Woo‐Jin; Lee, Jung Hyun; Lee, Sangyeop; Han, Dong‐Yeob; Kim, Jonghak; Park, Hyesung; Song, Hyun‐Kon; Park, Soojin
Abstract: A dendrite‐free and chemically stabilized lithium metal anode is required for extending battery life and for the application of high energy density coupled with various cathode systems. However, uneven Li metal growth and the active surface in nature accelerate electrolyte dissipation and surface corrosion, resulting in poor cycle efficiency and various safety issues. Here, the authors suggest a thin artificial interphase using a multifunctional poly(styrene‐ b ‐butadiene‐ b ‐styrene) (SBS) copolymer to inhibit the electrochemical/chemical side reaction during cycling. Based on the physical features, hardness, adhesion, and flexibility, the optimized chemical structure of SBS facilitates durable mechanical strength and interphase integrity against repeated Li electrodeposition/dissolution. The effectiveness of the thin polymer film enables high cycle efficiency through the realization of a dendrite‐free structure and a chemo‐resistive surface of Li metal. The versatile anode demonstrates an improvement in the electrochemical properties, paired with diverse cathodes of high‐capacity lithium cobalt oxide (3.5 mAh cm −2 ) and oxygen for advanced Li metal batteries with high energy density. Abstract : A multi‐functional block copolymer, which has a well‐balanced rigid‐soft character in chemical structure, flexibly controls the morphological structure of lithium metal anode as the breathable artificial interphase. This interphase further restrains the shuttle effect and chemical oxidation related to the anode corrosion through the hydrophobic and chemo‐resistive properties for high‐energy‐density and stable lithium metal batteries with diverse cathode materials.